The role of digital innovations in modernizing the social insurance system in Algeria -Case Study of chifa card in National Fund for employed workers’ Insurances- - ghafsi, toufik (Journal of Research in Finance and Accounting, 2023)
This study aims to highlight the effectiveness of digital innovations in modernizing the Algerian system of social insurance, which covers more than 80% of the population, this in shade of limited resources against the challenge of continuing to cover the increasing costs of health and social services for the social insureds. The research reached that the adoption of the electronic system for the chifa card in Algeria is a pioneering experience in the Arab world and Africa, it can be imitated in other ministries and sectors as part of the State's effort to adopt the electronic governance, where the generalization of the use of the chifa card by the CNAS allowed to achieve a set of benefits and objectives, the most important of which was represented in improving the quality of the provision of services to the social insureds, and increase the management efficiency, where the application of the system led to reduce the administrative costs by 7%.